2014
DOI: 10.1515/hmbci-2014-0004
|View full text |Cite
|
Sign up to set email alerts
|

Race differences in obesity and its relationship to the sex hormone milieu

Abstract: A sexual dimorphism exists in which increased abdominal and visceral adipose tissue (VAT) - found in women and marked by low sex hormone binding globulin (SHBG) and high bioavailable testosterone (BT) - is related to the metabolic risk profile. In men, increased BT is related to decreased abdominal obesity and a decrease in the metabolic risk profile. In women, race differences have been found in androgenic sex steroids including SHBG and BT as well as central fat distribution, creating inherently greater meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 89 publications
(117 reference statements)
0
7
0
Order By: Relevance
“…Women with markedly lower sex hormone-binding globulin (SHBG) and high bioavailable testosterone had increased abdominal and visceral adipose tissue. In men, increased bioavailable testosterone decreased abdominal obesity and metabolic risk profile [110]. The SWAN study showed that Black women had higher SHBG compared to White women, while both Black and Hispanic women had lower free androgen index (FAI) compared to White women, which is consistent with Black and Hispanic women having higher prevalence of obesity.…”
Section: Clinical Studies Of Gender Differences In Adipose Tissue Biomentioning
confidence: 88%
“…Women with markedly lower sex hormone-binding globulin (SHBG) and high bioavailable testosterone had increased abdominal and visceral adipose tissue. In men, increased bioavailable testosterone decreased abdominal obesity and metabolic risk profile [110]. The SWAN study showed that Black women had higher SHBG compared to White women, while both Black and Hispanic women had lower free androgen index (FAI) compared to White women, which is consistent with Black and Hispanic women having higher prevalence of obesity.…”
Section: Clinical Studies Of Gender Differences In Adipose Tissue Biomentioning
confidence: 88%
“…Although a previous meta-analysis revealed sex and age to be significant effect modifiers [7], we found no significant effect, and further studies may be warranted. Sex-related differences in CVD risk could be explained by variations in visceral adipose tissue accumulation, deposition, and distribution which have been associated with insulin resistance and metabolic risks [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we speculate that sex and growth hormones in difference races may also contribute sexual contrary relationship between circulating irisin and FPG. The changes of sex hormones show diverse in different ethnic groups, [ 26 , 31 ] which influence the muscle mass and adiposity. On the other hand, 1 study explored 36 girls with Turner syndrome after treating growth hormone.…”
Section: Discussionmentioning
confidence: 99%